Conceptual and Communicative Functions in Written Discourse - Ramlan Ginting Suka (Universitas Lampung, 2017)
Discourse is a general term for examples of language use, i.e., language which has been produced as the result of an act of communication. Whereas grammar refers to rules a language uses to form grammatical units as CLAURSE, and PHRASE, and SENTENCE, discourse refers to larger units of language such as paragraphs, conversations, and interviews. Sometimes the study of both written and spoken discourse is known as DISCOURSE ANALYSIS, some researchers however use discourse and TEXT LINGUISTICS to refer to the study of written discourse.Key Words: conceptual, communicative, discourse, text linguistics.